Effect of added rosemary extract on oxidative stability of Camelina sativa oil - Helena ABRAMOVIČ; Veronika ABRAM (Acta Agriculturae Slovenica)
The protective effect of added rosemary extract (RE) on the oxidative stability of highly unsaturated Camelina sativa oil was followed by periodic determination of its peroxide value (PV) during storage in darkness at room temperature. In camelina oil containing RE, a peroxide value of 10 mmol O2 / kg, the upper limit for unrefined oils, was not attained after 11 months’ storage. Compared to unprotected camelina oil the formation of hydroperoxides in oil containing RE was reduced by more than 40 %. The effect of RE against oxidation of camelina oil was also measured by the Rancimat test. In fresh camelina oil treated with RE the induction period was extended by 60 % as compared to untreated oil. Also, RE was more effective in preventing oil from oxidation when the oil was stored in darkness than in daylight.